PLANNING MAJOR SOURCES OF INFORMATION SPECIFIC GAME OF VOLLEYBALL (GYMNASIUM, 2009)
This paper aims to identify key factors specific to the game of volleyball during the course of itsgenerating information detrmină adapting the action of players.The determination of these sources of information and knowledge they generate information that canlead even fomarea habits to discover key issues that characterize a game situation.Such actions may be adjusted in game more effectively.